Who Is Employed? Evidence from Sub-Saharan Africa on Redefining Employment. (7th September 2022) - Gaddis, Isis; Oseni, Gbemisola; Palacios-Lopez, Amparo; Pieters, Janneke
Abstract: The 19th International Conference of Labour Statisticians (in 2013) redefined thelabour statistics standards, and most National Statistical Offices are currently transitioning to the revised standards. A major change, of which few academics seem to be aware, is that the concept of employment has been narrowed to work for pay or profit. By the revised standards, farming, which is mainly intended for own use, is no longer considered employment, and such a farmer is no longer considered to be employed or in the labour force. Instead, their work is captured under a new indicator of own-use production work. This paper analyses the implications of the revised standards on measures of employment in Sub-Saharan Africa drawing on specialised agricultural surveys from Ghana and Malawi and nationally representative multi-topic household surveys from two early adapters, Malawi and Nigeria. In some contexts, 70% to 80% of farmers produce for family consumption and are therefore, based on this activity, not considered employed by the revised standards; however, there is wide geographic variation. Moreover, farmers are more likely to produce for sale at the end of the growing season of the main local crop than earlier in the season. Men are more likely than women to produce for sale. Official labour statistics, based on the revised standards, show significantly lower employment-to-population ratios in rural Africa and give the impression of rural populations much less reliant on agriculture and much further along in the process of structural change than what was indicated by the previous standards.